YouTube and coronavirus: analysis of video consumption on the COVID-19 pandemic. - Gil-Ramírez, Marta; Gómez-de-Travesedo-Rojas, Ruth; Almansa-Martínez, Ana (Historia de los Sistemas Informativos, 2020)
Introduction: This research examines the typology of the consumption of the most reproduced videos on YouTube in relation to the early stages of the coronavirus crisis in Spain, categorizing the topics that obtained the most interest, the dates that recorded higher levels of consumption, and the typology of the uploaders that served as the main sources of information. Methodology: From a quantitative-qualitative perspective, is performed a content analysis of the 200 videos with the greatest impact between March 13 and April 13, 2020, based on the descriptors coronavirus and COVID-19. Results: The mass media channels, both Spanish and foreign, were the main sources of information about the status of the pandemic. The content focused on epidemiological data, followed by institutional communication, aroused the greatest interest. The consumption of videos increased after the decree of the State of Alarm, coinciding the peaks with the extensions of the decree, and with those times when the number of infections soars. Discussion and Conclusions: YouTube is operating on the COVID-19 pandemic as a depository platform for information from conventional media systems. It is significant the absence among of the main uploaders of WHO as an international health agency reference in decisions taken by most affected countries, which raises a reflection on the opportunity of strategic use of YouTube as a means of mass dissemination during public health risk situations such as the coronavirus crisis.
YouTube y coronavirus: análisis del consumo de vídeos sobre la pandemia COVID-19
Política de acceso abierto tomada de: https://nuevaepoca.revistalatinacs.org/index.php/revista/acceso_abierto
Keywords: COVID-19 - En los medios de comunicación social; Coronavirus; COVID-19; Pandemics; Media; YouTube; State of Alarm; Spain